Strengthening financial sustainability: Evaluating strategic revenue diversification at the sci-bono discovery centre, South Africa - Ntsobi, Mfanelo; Nyamkure, Blondel; Mwale, Bongani June; Nyingwa, Dumisani (International Journal of Economics, Business and Management Studies, 2025)
The study examines various evidence-based strategies for diversifying revenue streams to mitigate Sci-Bono's financial deficiencies and issues, aiming to decrease dependence on conventional sources. Social capital theory (SCT), in conjunction with resource dependency theory (RDT) and stakeholder theory, elucidates dependence on external resources and the necessity of stakeholder engagement in financing diversification, emphasizing the importance of networks and trust in obtaining funding options. The study employed a mixed-methods approach grounded in a pragmatic paradigm to encourage methodological heterogeneity. It incorporated qualitative interviews with significant stakeholders and quantitative surveys of relevant demographics to establish validity through triangulation, pilot testing, and member verification. The study utilized purposive sampling with 30 respondents possessing extensive knowledge of science centre operations. Qualitative data was analyzed through thematic techniques, and surveys for qualitative constructs employed NVivo and SPSS for qualitative and quantitative analyses, respectively. To ensure financial sustainability, the study considers government grants, business partnerships, and community-based initiatives, including crowdsourcing and local fundraising, as well as governmental policies. Based on effective case studies from various institutions worldwide, the research offers tips that enable Sci-Bono to diversify its funding sources. The report emphasizes that maintaining Sci-Bono's sustainability and expansion depends on a deliberate mix of thematic diversity, stakeholder involvement, digital visibility, and cooperation with both national and international organizations. The study concludes that Sci-Bono should prioritize strengthening relationships between companies and communities, utilizing digital channels to enhance outreach and support bases, and adopting science-aligned programs to diversify income streams.